The neuroprotective activity of tamoxifen and tibolone during glutathione depletion in vitro - Belenichev, I. F.; Odnokoz, O. V.; Pavlov, S. V.; Belenicheva, O. I.; Polyakova, E. N.; Бєленічев, Ігор Федорович; Однокоз, О. В.; Павлов, Сергій Васильович; Бєлєнічева, О. І.; Полякова, Є. Н. (Moscow: Pleiades Publishing, Ltd., 2012)
Abstract—Modulators of estrogen receptors play a significant role in cerebral activity and in the regulation of vital functions of the whole organisms. This work objective is to enlarge knowledge of Tamoxifen neuroprotective action and to determine neuroprotective action of Tibolone (both are modulators of estrogen receptors) studying their influence on antioxidant system indices, oxidative stress and mitochondrial dysfunction caused by glutathione depletion of neurons in vitro. Depletion of glutathione by buthionine sulfoximine (BSO) in neurons leads to displacement of the thiol_disulfide equilibrium in vitro. Introduction of BSO into neuron suspension results in a decrease of reduced glutathione (GSH) level and in an increase of oxidized glutathione (GSSG) level. It was also shown an activity suppression of antioxidant enzymes. That results in the onset and develop_ ment of oxidative (increase in oxidative protein destruction markers level) and nitrosative (increase in 3_nitrotyrosine level) stresses. These disturbances lead to mitochondria dysfunction resulting as a rule in apoptotic neuron death. Tamoxifen and Tibolone (0.1 μM) normalize thiol_disulfide balance and significantly reduce the risk of oxidative and nitrosative stresses. That way, they prevent mitochondria dysfunction and cell death.
Keywords: glutathione; mitochondrial dysfunction; tamoxifen; thiol-disulfide system; tibolone; HSP 70; protein carbonyls